Double pylorus: case report and review of the literature - Safatle-Ribeiro, Adriana Vaz; Ribeiro Júnior, Ulysses; Habr-Gama, Angelita; Gama-Rodrigues, Joaquim J. (Revista do Hospital das Clínicas, 1999)
Double pylorus is an unusual condition in which a double communication between the gastric antrum and the duodenal bulb occurs. It may be congenital, or it may be acquired complication of peptic ulcer disease. We present a case of double pylorus in a gentleman with epigastric pain and previous history of peptic ulcer disease. The relationship between Helicobacter pylori and this disease was assessed. A review of the literature, the role of associated diseases and the role of H. pylori are discussed.